Properties of Palm Oil Ash Geopolymer Containing Alumina Powder and Field Para Rubber Latex - Abideng Hawa; Preecha Salaemae; Akkadath Abdulmatin; Krittiya Ongwuttiwat; Woraphot Prachasearee (Civil Engineering Journal, 2023)
Most geopolymer binder is produced using raw materials comprising powder with high silica and alumina content. Additionally, fine aggregate is prepared with river sand for high bulk density. This research proposes using palm oil ash (POA) for the main binder and palm oil clinker (POC) for the fine aggregate. The chemical composition of POA has high levels of silica but low alumina, so it must undergo partial replacement with alumina powder (AP). POA and POC are waste by-products of electrical power plants. The properties to be investigated include compressive strength, bulk density, water absorption, and microstructure. The effect of mixture composition, i.e., POA and field Para rubber latex (FPRL), on those properties is of particular interest. POA was substituted by AP and FPRL at 2.5%, 5%, 7.5%, and 10%, and at 1%, 3%, 5%, and 10%, respectively. Geopolymer mortars were cured at ambient temperature for 24 hours and kept at ambient temperature until testing. The compressive strengths of the geopolymer mortars were tested at 1, 7, and 28 days. The results showed that the optimal mixture consisted of 5% AP in the case of AP only and 1% FPRL in the case of FPRL only, while the ternary optimal mixture of 1% FPRL and 7.5% AP achieved higher compressive strengths than the control (CT) sample at 28.16, 19.98, and 25.30 MPa, respectively, after 28 days of curing. Bulk density increased with the addition of AP and FPRL. The microstructures of the geopolymer samples investigated using SEM-EDX showed the presence of different elements with different mixtures and displayed a dense, compact geopolymer matrix with high compressive strength. Using large amounts of POA in combination with AP and FPRL improved the environmental aspects of landfill disposal. Doi: 10.28991/CEJ-2023-09-05-017 Full Text: PDF